Efektivitas Ekstrak Etanol Buah Makasar (Brucea Javanica) terhadap Penurunan Kadar Asam Urat Mus.Musculus Jantan - eka lokaria; Ivoni Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to find out the effectiveness of ethanol extract of makasar fruit (Brucea Javanica) against the decrease in uric acid levels of male Mus Muculus. This research is an experimental study using RAL technique using male mencit test animals, Treatment 4 groups divided into P0 (Aquades), P1 (Allopurinol 10 mg/g BB) P2 (chicken liver extract + 100 mg/kgBB), P3 (chicken liver + extract 200 mg/kgBB). The administration of makasar fruit extract can lower the levels of squeaky uric acid induced by the suspension of chicken liver. The administration of makasar fruit extract based on the average value is better in lowering blood uric acid levels than allopurinol drugs, based on different tests with LSD method of decreasing uric acid levels in the positive control group and the treatment group did not have a meaningful difference (p ≥ 0.05). In conclusion, makasar ethanol extract (Brucea Javanica) effectively significantly lowers the uric acid levels of male Mus Muculus than the drug allopurinol, but has no meaningful difference between the treatment group and the control group. Keywords: Fruit makasar, Decreased Uric Acid Levels, Mus. Male Musculus